Preservation Efforts of Pranajiwa (Euchresta horsfieldii (Lesch.) Benn.) Based on Tri Hita Karana by Balinese Community - Rubangi Al Hasan; Krisnawati Krisnawati; Anita AD Rahayu (Jurnal Wasian, 2022)
Pranajiwa (Euchresta horsfieldii (Lesch.) Benn.) has been widely used as traditional medicine by the Balinese ethnic community. Up to now, the raw materials for traditional medicines from E. horsfieldii are harvested directly from their natural habitat. It is feared that it will interfere with its sustainability. The Balinese ethnic community has a culture known as the Tri Hita Karana (THK) concept, which means there is a balance in the relationship between humans and God, nature, and with fellow humans. This study aims to identify the use of E. horfieldii and its conservation efforts based on THK. This research was carried out in communities living around Bedugul, Bali. The method of data collection was done by participatory observation and semi-structured interviews. The research informants were 33 people with a purposive sampling method. The criteria are based on the level of knowledge and use of E. horsfieldii. Data were analyzed and interpreted descriptively. The results of this study indicate that E. horsfieldii has been widely used to treat various diseases and is practiced by many traditional healers (balian). However, people also use it for treatment without a standardized dose. This causes the measure of its use is very diverse. Harvesting of E. horsfieldii is carried out by the community while still observing the principle of sustainability according to the THK philosophy. Harvesting of E. horsfieldii is mostly done for individual needs. Although there has been a practice of buying and selling E. horsfieldii, harvesting has not resulted in over-exploitation. Efforts to conserve E. horsfieldii have been carried out by the community, especially the balians by trying to cultivate it, although they still fail. In addition, the conservation of E. horsfieldii is carried out by the Bali BKSDA with efforts to maintain the habitat of E. horsfieldii in forest areas.      Keywords: Euchresta horsfieldii, balian, preservation effort, traditional medicine